Model Pendidikan Non-Formal pada Pencegahan Penyalahgunaan Narkoba di Kelurahan Air Hitam: Studi pada Program Kelurahan Bersinar - Chantika Riski Ananda; Arif Sugianto; Wahdatan Nisa; Husnawati Husnawati (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aims to analyze the community-based education model on the implementation of the Shining Village Program in an effort to prevent drug abuse in Air Hitam Village. The method used in this study is a qualitative method to in-depth examine the process of program implementation in the community. The data collection technique was carried out through document studies and evaluation using the Self-Resilience Index (DEKTARI) questionnaire filled out by adolescent program participants. Data analysis techniques use data reduction, data presentation, and conclusion drawing. The results of the study show that the implementation of the Shining Village Program is carried out through three main stages, namely planning, implementation, and evaluation. The planning stage is carried out through the identification of needs and determination of target areas based on the drug trafficking vulnerability index. The implementation stage is carried out through the formation of peer youth groups, socialization activities about the dangers of drugs, and training classes such as public speaking to improve communication skills and adolescent resilience. The evaluation stage was carried out through filling out the Self-Resilience Index questionnaire (DEKTARI) to find out the level of self-resilience of adolescents in rejecting drug abuse. Thus, the Shine Village Program based on community education can be an effective effort to increase awareness, knowledge, and the active role of adolescents in the prevention of drug abuse in the community.